Cysteine 203 of Cyclophilin D Is Critical for Cyclophilin D Activation of the Mitochondrial Permeability Transition Pore - Nguyen, Tiffany T. (American Society for Biochemistry and Molecular Biology, 2011)
The mitochondrial permeability transition pore (mPTP) opening plays a critical role in mediating cell death during ischemia/reperfusion (I/R) injury. Our previous studies have shown that cysteine 203 of cyclophilin D (CypD), a critical mPTP mediator, undergoes protein S-nitrosylation (SNO). To investigate the role of cysteine 203 in mPTP activation, we mutated cysteine 203 of CypD to a serine residue (C203S) and determined its effect on mPTP opening. Treatment of WT mouse embryonic fibroblasts (MEFs) with H(2)O(2) resulted in an 50% loss of the mitochondrial calcein fluorescence, suggesting substantial activation of the mPTP. Consistent with the reported role of CypD in mPTP activation, CypD null (CypD(−/−)) MEFs exhibited significantly less mPTP opening. Addition of a nitric oxide donor, GSNO, to WT but not CypD(−/−) MEFs prior to H(2)O(2) attenuated mPTP opening. To test whether Cys-203 is required for this protection, we infected CypD(−/−) MEFs with a C203S-CypD vector. Surprisingly, C203S-CypD reconstituted MEFs were resistant to mPTP opening in the presence or absence of GSNO, suggesting a crucial role for Cys-203 in mPTP activation. To determine whether mutation of C203S-CypD would alter mPTP in vivo, we injected a recombinant adenovirus encoding C203S-CypD or WT CypD into CypD(−/−) mice via tail vein. Mitochondria isolated from livers of CypD(−/−) mice or mice expressing C203S-CypD were resistant to Ca(2+)-induced swelling as compared with WT CypD-reconstituted mice. Our results indicate that the Cys-203 residue of CypD is necessary for redox stress-induced activation of mPTP.